Report of the Committee on Public Institutions relative to impressment of buildings : February 24, 1864 (Document (Virginia. General Assembly. Senate) ;, 1864)
1864 Report of the Committee on Public Institutions regarding the impressment of various state buildings by the Confederate government. The committee recommended resolution which would require restoration of the deaf and dumb asylum and the female institution, both in Staunton, back to their respective trustees.